Humanisme, Pendidikan dan Al-Qurâan (Menelaah Pemikiran Ki Hadjar Dewantara) - Rahman, Syaifur (Humanistika : Jurnal Keislaman, 2017)
Abstract:Education is still one effective way to raise the dignity of a nation, because of the quality of the educational process it will form the next generation of quality, and vice versa. But unfortunately education in Indonesia is still a tool group that has more power to dominate against the weaker group. The rich still feel entitled to the poor, the clever more entitled to school than the fool, the teacher is smarter than the learner, so that those who feel more than others also feel entitled to oppress, violence, injustice etc. . Yet if this proceeds will only form a vicious cycle of evil because the oppressed party will become the next oppressor when it has a chance, and so on so that no one will benefit. One proof of the loss of human values in the education process is the spread of violence cases that not only put a child or learners as victims, but also many of the learners who have been incarnated as the perpetrators of violence, ranging from brawls to raids that are not only disadvantageous materially but also have many lives that drifted in vain. This is the reality of educational outcomes that are not based on human values, but focusing on the attainment of the completeness of the curriculum without regard to moral and social aspects, especially education should be able to accommodate all the potential that is in each learner, so that they grow and develop according to that potential. To restore human dignity through education is to organize humanism education. This view considers that human beings as having the basic potentials that need to be developed in the educational process, for which education should be carried out with full humanitarian values and see that learners have had the basic potential in them (humanism) what they need is the guidance, direction and guidance of a teacher, which is why Ki Hadjar said that a teacher should be able to be among the skills of momong and ngemong. The ultimate goal of an education is the formation of self-awareness of each learner, with that awareness they will be able to assume responsibility as the backbone of a nation. for that is in the middle of the fourth industrial revolution era that occurs today it is important to restore the values of humanity in education, do not let the human likened to items such as robots or empty bottles are ready to receive any knowledge from the teacher. In addition according to Ki Hadjar a teacher is an important figure in the process of realization of quality education, the spearhead of the implementation of humanism education process is a teacher. a teacher must have a comprehensive world view associated with the learner and its development, therefore a teacher must equip themselves with various sciences such as psychology, or physiology so they can direct the potential that exists in each learner. educate is not enough on instinct alone, because diverse learners will need a diverse approach as well for that is important for teachers to equip themselves with various educational sciences.Keyword: Humanism, Al-Qurâan, Education